Pengaruh Current Ratio, Debt to Equity Ratio dan Ukuran Perusahaan Terhadap Rating Obligas Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2016 - Ade Tiya Kurnia Wati (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
ABSTRACT This study aims to determine the effect of current ratio, debt to equity ratio and firm size (size) against the rating of bonds in banking companies listed on the Indonesia Stock Exchange 2012-2016. This type of research is a correlational research. The population of this study is a banking company listed on the Indonesia Stock Exchange amounted to 31 companies. The sampling technique used in this study is purposive sampling with the following conditions: (1) The banking company listed on the Indonesia Stock Exchange from 2012-216; (2) The banking company with bond rating issued by PT. Pefindo in the study period, 2012-2016; (3) The banking company that has data in the form of financial statements required in this study. The sample of this study amounted to 9 banking companies. Technical analysis used in this study is multiple linear regression with the help of SPSS program. The results of the study showed that: (1) Current ratio has no effect on bond rating with coefficient value 0,002 and sig 0,502 (2) Debt to equity ratio has no effect on bond rating with coefficient 0,00 and sig 0,412 (3) have a positive effect on bond rating with coefficient value 0,05 and sig 0,001. .